-7x-3(5x-6)=-38

Simple and best practice solution for -7x-3(5x-6)=-38 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x-3(5x-6)=-38 equation:



-7x-3(5x-6)=-38
We move all terms to the left:
-7x-3(5x-6)-(-38)=0
We add all the numbers together, and all the variables
-7x-3(5x-6)+38=0
We multiply parentheses
-7x-15x+18+38=0
We add all the numbers together, and all the variables
-22x+56=0
We move all terms containing x to the left, all other terms to the right
-22x=-56
x=-56/-22
x=2+6/11

See similar equations:

| 9/6w=18 | | 4n+16=24n | | -5(m+1)-m-14=-6(m+4)+5 | | 12x54=-8x-4(-5x+2) | | 9f=1/2(6f-1) | | X+6=x+0=3x-31 | | 4(n+4)=6(4n) | | -15+3b-19=14+19b | | -3x+5x-9=2(x-6)-3 | | -1+7h=17+8h | | (7y+16)(3y+22)=0 | | 80-x=368 | | 2.9x-12.32=4.5 | | -4.8/1.5=1.5z/1.5 | | 9x+42=4x+2 | | 8x-1=3x+5+3(x-5) | | 7/13n=13/14 | | 2x3 +55=1 | | 9/7(s)=-1/3 | | n+4/4=6/4 | | 9=-16t^2+16t+9 | | 9/7s=1/3 | | u-4/2=4/3 | | 10(x-3)+15=8x+7 | | 4.2x-6.66=7.2 | | 10−9x2+4x=−6x2 | | 2.1x-4.27=3.5 | | 2x+x+18=66 | | 10-(x-9)=7x-7 | | 5x+23=0 | | d/3+4=-12 | | 3(3+m)+5m=5(2m-1) |

Equations solver categories